HEAT DISSIPATION ON THE LATERAL SURFACE OF CYCLONE CHAMBER WITH ASYMMETRICAL TWO-WAY GAS INPUT AND OUTPUT - E. N. Saburov; N. V. Smolina (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The heat dissipation on the lateral surface of the cyclone chamber working volume with asymmetrical input and output of gases is considered in the present paper in contrast to the previously executed [1–10]. The relative values of input gas flow and the relative diameters of the outlet are different in each of the halves of the working volume. The heat dissipation by convection to the swirling airflow was studied by the method of variation of the aggregate state of the heating agent – water vapor slightly superheated (at 2–3 °С) condensation. Collecting the condensate produced from the work site through a water lock, providing maintaining of constant pressure in the calorimeter. The quantity of heat transmitted during the experiment was determined by the amount of collected condensate.In the experiments on the camera with two-sided asymmetric output relative gas outlet diameter on one side of the camera varied Relative diameter of the outlet on the other hand remained constant. In the experiences on the camera with the bilateral asymmetrical conditions for the introduction of gases the asymmetry of the introduction of flow was created due to a change in the relative entrance area whoo remained constant. Local heat transfer coefficient was determined for different values dimensionless longitudinal coordinate coinciding with the axis of the chamber, directed toward the outlet, measured from the middle section of the working volume. Еquations for calculation of heat transfer coefficients on the lateral surface of the howling cyclone chambers with unbalanced input and output gases, оbtained in this paper, give the satisfactory agreement of the calculated and experimental data that allows to recommend to their practical application.